Deteksi sistiserkosis pada babi yang dipotong di Rumah Potong Hewan Kota So’e - Meriany Presty Alvianita Tamonob; Annytha I.R Detha; Diana A Wuri (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2019)
Cysticercosis is a disease caused by the larvae of Taenia sp. worm which have serious impact to human. One of many caused of cysticercosis is population and maintenance system in a region. TTS is one area that has the highest number of pigs in the province. This study aims to determine the cysticercosis of pig at the slaughterhouse in So’e and to know the relation between cycstisercosis and maintenance system. The study was conducted to 14 pigs. The examination performed on the tongue muscle, masseter muscle and liver. The test were conducted postmortem examination and laboratory test. Laboratry test conducted to identify morphological of skoleks. The changes in the organs of the result of postmortem examination continued to cysticercus identification. And the laboratory result showed that 2 pig positive cysticercosis caused by cysticercosis cellulosae. It can be included that the cysticercosis connected with maintenance system. However, the cysticercosis of pig in So’e still required program by relevant agencies to eradicate this disease.